A study on the relationship between work life culture and employees' satisfaction at Pejabat Daerah Dungun / Nur Zahirah Mohd Zahali - Mohd Zahali, Nur Zahirah (Faculty of Business and Management, 2018)
The purpose of this research was to study the relationship between work life culture and employees' satisfaction at Pejabat Daerah Dungun in Terengganu. There are four factors of work life culture which is job sharing, childcare support, employees' welfare and wellness program. Due to that, the method used in this study was Correlational Research. This study has used simple random sampling as the sampling technique. 66 questionnaires were distributed to the employees at Pejabat Daerah Dungun by hand. A cover letter also attached in each questionnaire. The questionnaire consist of three (3) sections which are section A, B & C. In this study, there are consist of three research objectives that need to identify. The first research objective was to identify the factors of work life culture that will affect employees' satisfaction at Pejabat Daerah Dungun in Terengganu. The second research objective was to identify the factor of work life culture that are most influence employees' satisfaction at Pejabat Daerah Dungun in Terengganu. The third of research objective was to determine the relationship between work life culture and employees' satisfaction at Pejabat Daerah Dungun in Terengganu. The majorities of the respondents were male with and for dimension of age were age between 36 to 40 years, the marital status were married and has children. Majority of their job position was clerk, the level of education most of respondents had SPM and had service more than 20 years. Moreover from the results, there was a positive relationship between all of factors of work life culture and employees' satisfaction. In order to make some improvement to the employees, there were several recommendations and suggestions were stated by the researcher.